CENTRIFUGAL METHOD OF PRODUCTION OF ZIRCONIUM MICROSAMPLES FOR ISOTOPE DATING OF ROCKS - Ajriyants A.A.; Rudnev S.N.; Kruk N.N.; Vladimirov A.G.; Yusupov T.S. (My University, 2001)
Process of separation of accessory minerals has been considered. It has been shown, that traditional methods of separation of the minerals are non-efficient. In order to improve efficiency of zircon extraction from granite, other methods of separation have been tested. Results of the tests have shown that application of 'Knelson' concentrator is successful method. Method of gravitational separation of heavy accessory minerals from rocks with the use of 'Knelson' concentrator has been developed.